Implementation of CSR in Environmental Social Accounting Realizing Corporate Responsibility for Sustainability and Community Welfare - Wahyuni, Wahyuni; Farman, Safril; Suaib, Muh. Rifki; Suaib, Suci Rahmadani (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study examines the integration of Corporate Social Responsibility (CSR) into environmental social accounting to promote corporate sustainability and community welfare. The goal is to assess how CSR practices contribute to long-term corporate value while ensuring transparency in reporting social and environmental impacts. Research Design and Methodology: The research employs systematic literature review methodology, analyzing academic papers, reports, and case studies on CSR and environmental social accounting. The review identifies frameworks and practices that help companies measure and report CSR outcomes effectively. Findings and Discussion: The study highlights the effectiveness of CSR integration in enhancing corporate reputation, stakeholder trust, and sustainability efforts. It also identifies challenges in reporting consistency, mainly due to the lack of standardized frameworks, which can lead to discrepancies in evaluating CSR performance. The role of technology in improving CSR reporting accuracy and transparency is emphasized. Implications: The research offers practical insights for businesses integrating CSR into their operations. It suggests adopting standardized reporting frameworks and digital tools for better data collection. These steps will enhance CSR’s impact on corporate performance and community welfare, fostering long-term sustainability.